Parity between advanced training qualifications and university degrees: ultimately the labour market decides - Weiß, Reinhold [Verfasser] (My University, 2011)
"Recent years have seen a marked increase in the numbers completing the transition into higher education. The target of 40 per cent of an age cohort embarking on a degree programme has not only been achieved but surpassed. It is only a matter of time before this trend pays off in the form of higher numbers of graduates in the German labour market, exposing skilled workers who have qualified via the vocational pathway to heightened competition. As yet, it remains to be seen what impact this will have on different occupations and sectors. Meanwhile it is all the more important to make progress in the direction of permeability and parity between educational pathways, so that people with vocational qualifications can take advantage of the opportunities." (Autorenreferat, BIBB-Doku)
Keywords: G 1.3.1 Bildungsangebot & -nachfrage; G 2.5.3 Anschlussfähigkeit von Bildungsgängen; Berufsabschluss; Aufstiegsfortbildung; Studienabschluss; Durchlässigkeit im Bildungssystem; Arbeitsmarkt